Evaluation of Community-Based Conservation Policy for Wildlife Management in Nigeria - Agboola, Olugbenga O.; Oluwole, Ajayi; Tijani, Nasiru O. (ABUAD Journal of Social and Management Sciences, 2022)
This study evaluates community-based conservation policy for wildlife management in Nigeria. The research focuses on the laws, polices and act promulgated to protect and preserve our environmental landscape from degradation by identifying National Park Act as the most suitable law for the study. The research relies extensively on secondary data sources especially articles on community based conservation. Findings reveal that, though community based conservation has been integrated into the National Park Service Act, it is yet to be fully implemented in all the parks. Records have it that the Act is in operation in Cross River National Park, Old-Oyo National Park, and Kainji Lake National Park. However, even in places where the Act is being implemented, hunters, poachers, farmers and livestock farmers still encroach and cause degradation in these protected areas. The study concludes that community based conservation policy has proved to be a framework which can guide conservation and incorporate host communities in the administration of the protected areas. The policy further enhances community participation and the involvement of the locals in the management and conservation of natural resources. This form of community participation is a vital instrument in environmental resources management. The study therefore recommends that community-based conservation policy should be implemented to the letter to curb environmental degradation and promote community involvement. Also, community members should be involved in the planning and conservation of natural resources. In addition, empowerment programmes should be provided as an alternative means of livelihood for the local people in other to reduce over dependence on environmental resources.